Hubungan Tipe Kepribadian Berdasarkan MBTI (Myers-Briggs Type Indicator) dengan Hasil Belajar Ekonomi Siswa Kelas XII IPS - Rahmiati, Friska; Caska, Caska; Sari, Filma Alia (Peneliti.net, 2025)
This research seeks to examine the connection between students’ personality types, as identified through the MBTI (Myers-Briggs Type Indicator) and their economic learning outcomes of twelfth-grade social science students at SMAN 15 Pekanbaru. Personality types can influence students' learning styles and understanding of the material, making it essential to understand these personality types to improve learning outcomes. This research employs a correlational method with a quantitative approach. It was carried out at SMAN 15 Pekanbaru with a sample of 100 twelfth-grade social science students. Data were collected via documentation and questionnaires. The data were analyzed using descriptive statistical analysis, Kolmogorov-Sminrov test, and the Spearman Rank correlation test, with the help from SPSS version 23. The findings of this research suggest a positive, yet very weak and not significant, relationship between students’ MBTI personality types and their economic learning outcomes. The correlation coefficient which stands at 0.102, reflects a very weak relationship, and with a significance value of 0.313 well above the 0.05, threshold this relationship is not statistically meaningful. Personality types only contribute 4,2% to economic learning outcomes. The other 95,8% is likely driven by various external and internal factors that were not explored in this research.